2004
DOI: 10.1016/j.femsec.2004.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide production in a forest soil at low temperatures – processes and environmental controls

Abstract: Recent investigations have highlighted the relative importance of the winter season for emissions of N(2)O from boreal soils. However, our understanding of the processes and environmental controls regulating these emissions is fragmentary. Therefore, we investigated the potential for, and relative importance of, N(2)O formation at temperatures below 0 degrees C in laboratory experiments involving incubations of a Swedish boreal forest soil. Our results show that frozen soils have a high potential for N(2)O for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 41 publications
(69 reference statements)
5
46
0
Order By: Relevance
“…It is clear from our study that freeze-thawing increased microbial activity (as evidenced by the increasing CO 2 production) and the expression of denitrifying genes, which lead to the release of N 2 O gas. This supports the view that the flush of N 2 O and CO 2 is a result of increased microbial activity during the dynamic event of freeze and thaw (5,6,16,24,33), instead of mere entrapment of gases due to the freeze barrier. However, this was a microcosm experiment under controlled conditions, and the freeze-thaw process was laboratory simulated.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…It is clear from our study that freeze-thawing increased microbial activity (as evidenced by the increasing CO 2 production) and the expression of denitrifying genes, which lead to the release of N 2 O gas. This supports the view that the flush of N 2 O and CO 2 is a result of increased microbial activity during the dynamic event of freeze and thaw (5,6,16,24,33), instead of mere entrapment of gases due to the freeze barrier. However, this was a microcosm experiment under controlled conditions, and the freeze-thaw process was laboratory simulated.…”
Section: Discussionsupporting
confidence: 83%
“…Ö quist et al (24) reported the source of N 2 O to be denitrification occurring in anoxic microsites in frozen soil, before thawing. However, there have been no reports correlating gas emissions to the diversity and quantity of denitrifying genes and transcript during the freezethaw process.…”
Section: Discussionmentioning
confidence: 99%
“…The soils are more mature than soils in the high arctic with a significantly larger microbial biomass, greater concentration of labile carbon and considerably more C min . In each of the soils studied there was evidence of considerable ammonification as temperatures rose from −10 • C. N min occurred in certain soils simultaneously both above and below the freezing point which is consistent with previous studies in the arctic and sub-arctic (e.g., Schimel and Clein, 1996;Schimel and Mikan, 2005;Oquist et al, 2004;Miller et al, 2007). There is little doubt that ammonification is more active as the temperature rises but so is the immobilisation of R. Guicharnaud et al: Short term temperature changes of microbial processes in Icelandic soils resultant NH + 4 as activity per unit of microbial biomass increases.…”
Section: Soil Locationsupporting
confidence: 90%
“…In this area a general consensus has been reached, and most of the literature has found denitrification to be the dominant processes inducing freeze-thaw N 2 O emissions (Müller et al 2002;Müller et al 2003;Ludwig et al 2004;Öquist et al 2004;Sehy et al 2004;Koponen et al 2006b;Mørkved et al 2006;). This conclusion has been reached through several methods of experimentation.…”
Section: N 2 O Production Pathways As Contributors To Freeze-thaw Emimentioning
confidence: 99%